Paradoks Kebijakan Arak Bali: Pelestarian Budaya dan Pengendalian Dampak Negatif - Mahadewi, Anak Agung Istri Wulan Kharisma; Larasati, Nadia Utami (Jurnal Ragam Pengabdian, 2026)
Arak Bali is an intangible cultural heritage with religious, social, and economic significance for Balinese society, yet it is also vulnerable to misuse as a recreational alcoholic beverage. Bali Governor Regulation Number 1 of 2020 was enacted to protect Balinese traditional fermented and distilled beverages while controlling their negative impacts. This study aims to analyze the policy paradox and the mechanisms for controlling the negative impacts of arak Bali through the perspective of Travis Hirschi’s Social Control Theory. A qualitative descriptive approach was employed using in-depth interviews with five key informants, supported by participatory observation and literature review. The findings reveal that the regulation has strengthened legal protection and increased the economic value of arak Bali for local artisans, but has also encouraged a shift in its meaning from a sacred ritual object to a commercial commodity. The negative impacts are controlled through formal mechanisms involving government and law enforcement agencies, and informal mechanisms through traditional villages, banjar, pecalang, and awig-awig. The study concludes that policy effectiveness depends on the synergy between formal regulation and culture-based social control in Balinese society.